Interfacial triboelectrification-modulated self-recoverable and thermally stable mechanoluminescence in mixed-anion compounds - Bai, Yongqing; Wang, Fu; Zhang, Liqiang; Wang, Daoai; Liang, Yongmin; Yang, Shengrong; Wang, Zhaofeng (Nano energy, 2022)
In this work, the mechanoluminescent performance of the rare earth-doped mixed anion compounds, Sr3Al2O5Cl2:Ln (Ln = Eu2+, Tb3+, Ce3+), is reported. Different from the conventional piezoelectricity-involved ones, the as-observed mechanoluminescence in Sr3Al2O5Cl2:Ln is non-piezoelectrical, suggesting that there should be distinct physical processes that bridge the macroscopical mechanics stimuli to the microscopic electron transfer. By comprehensively investigating the thermoluminescence, cathodoluminescence and triboelectricity properties as well as the matrix effects, an interfacial triboelectrification-induced electron bombardment model with the direct excitation-emission process is demonstrated and established. The unique mechanoluminescent processes endow the Sr3Al2O5Cl2:Ln with temperature-modulated self-recovery activities and prominent thermal stability, based on which two types of intriguing devices regarding the visualized temperature sensing and the multi-mode information storage are developed. The findings in this work provide a deep insight on the non-piezoelectrical mechanoluminescence from fundamentals to device applications, which show great guiding significance for the future mechanoluminescence design and applications. [Display omitted] •Self-recoverable mechanoluminescence was obtained in non-piezoelectric compounds.•The interfacial triboelectrification-induced electron bombardment model was established.•The unique physical processes endowed the material prominent thermal stability.•Visualized temperature sensing and multi-mode information storage devices were developed.